Character Formation through Quranic Memorization Programs: An Educational Management Approach - Syahweli, Fahril; Rahmi, Ulva (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
Quranic memorization programs serve as an important instrument in fostering students’ character and behavioral development. This study aims to examine the influence of Quranic memorization program management on character formation and behavioral development among elementary school students. A quantitative approach was employed using a survey method. The sample consisted of 120 students selected through stratified random sampling. Data were collected using a Likert-scale questionnaire (1–5) and analyzed using Structural Equation Modeling (SEM) with LISREL 8.80. The results indicate that the management of the Quranic memorization program has a positive and significant effect on students’ character (t-value = 6.72) and behavioral development (t-value = 5.94). The SEM model demonstrates a good fit, as indicated by χ² = 142.18, RMSEA = 0.045, CFI = 0.97, and GFI = 0.93. These findings confirm that well-structured management of Quranic memorization programs contributes substantially to enhancing students’ religiosity, discipline, responsibility, and social behavior.